Socio-psychological methods of public administration - Silechnik, M. (My University, 2021)
Management of state social processes is carried out using various methods that allow the interaction between the object and the subject so that the main strategic, operational and tactical goals are achieved with maximum effect throughout the state. The management method is a set of techniques, methods, means of ensuring the desired result. Methods determine the management quality side: improving them means improving management. Public administration methods can be general, special, administrative, economic, sociopsychological and others used in public administration.
Keywords: public administration; methods; anagement; result; socio-psychological methods